GE-APROAch: an OBEdized survey instrument on GenEd outcomes achievement based on student personal reports - Rivera, Rodrigo C.; Delos Santos, Elymae Naldo; Ofracio, Juan Oliver S. (International Journal of Evaluation and Research in Education (IJERE), 2025)
The Philippine commission on higher education (CHED) requires colleges and universities to align with its triad goals of individual, social, and global development, through the new general education curriculum (NGEC). Since its implementation, numerous studies have evaluated outcomes, often reporting positive results. However, these studies exhibit methodological inconsistencies due to varying assessment measures. While two studies from the same college employed robust self-developed instruments based on CHED standards to evaluate general education (GE) outcomes, questions about their reliability led to the creation of the GE-assessment of personal reports of outcomes achievement (GE-APROAch) instrument. Using a mixed-method descriptive-evaluation design, the research constructed and validated the instrument. Results indicated that the GE-APROAch effectively measures GE outcomes through: i) a solid conceptual framework of targeted competencies; ii) high interrater agreement from expert judges; iii) strong internal reliability to differentiate and consistently report scores; and iv) superior efficacy compared to existing tools. Establishing the validity of self-made instruments is crucial, particularly for evaluating curriculum learning outcomes. Statistical analysis confirms that the GE-APROAch is a reliable and valid tool, offering improvements over previously used instruments.